Criminal procedure reform and the impact on homicide: evidence from Mexico - Huebert, Erin Terese (Trends in organized crime, 2021)
While significant efforts have been made to reform the criminal justice system across Latin America, we do not know the conditions under which reform effectively deters homicide, one of many goals of the reform. Drawing on a novel sub-national design in Mexico, I find that criminal procedure reforms aimed at improving due process are not sufficient for deterring homicide in places where non-state actors (i.e. drug cartels) effectively challenge the state’s monopoly of violence. I argue that in these settings, citizens are less willing to cooperate with the formal system of justice - despite reform efforts. Without society cooperation, the prosecution is less equipped to investigate, prosecute, and solve crime, resulting in impunity and little deterrence. Importantly, where the state maintains its monopoly of violence, reform is associated with less homicide. In selecting remedies to combat violent crime, therefore, different communities need to pursue different strategies, suggesting that the State can deter violence through fairness.